Potential of GTL biosolids in a circular economy: investigating blending, pyrolysis, activation, and characterisation - Shifa Zuhara (14150862) (2023)
Qatar’s population has been rapidly increasing in recent years, and the country’s long-term vision, QNV 2030, aims to sustain this growth by transforming the country into a sustainable state. One aspect of this vision is to convert waste into value-added products, which will reduce the environmental and spatial burden associated with waste in Qatar, while contributing to a circular economy. This study describes methods for producing biochar and activated carbon (AC) from gas-to-liquids derived biosolids, cardboard waste and mixed samples using pyrolysis and activation techniques. The characterisation of products revealed that the yield of biochar samples was higher than AC, and that the pH of the biochar samples was more alkaline than the feed samples due to metals after pyrolysis and reduced acid surface functional groups. Proximate analysis of samples showed lowered moisture and enhanced ash in feeds upon pyrolysis and activation due to increased temperature with reduced volatile content. AC application to water treatment is considered a potential benefit due to the increased surface area, pore volume and magnetic properties based on the Brunauer–Emmett–Teller (BET) and X-ray Powder Diffraction (XRD) analysis. The X-ray photoelectron spectroscopy (XPS) analysis also showed increased –CO3/O–C = O and potassium in the ACs as a result of potassium carbonate activation. The study proposes various applications that can support a circular economy, but future studies should investigate actual applications and potential health and environmental effects and evaluate the feasibility and environmental impact of production methods. Other Information Published in: Environmental Technology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/09593330.2023.2238929